Dominant communities and dominant designs: Community-based innovation in the context of the technology life cycle. (May 2017) - Seidel, Victor P; Langner, Benedikt; Sims, Jonathan
Online community–based innovation—whether through self-organized communities, firm–community collaborations, or innovation contests and crowdsourcing—is increasingly used as a source of technological advances, yet studies in this domain are often detached from considering the dynamics of technological evolution itself. Where technological advances reside (knowledge distribution), the degree to which innovation tasks can be specified (task decomposition) and the rate of technological progress (performance trajectory) all vary dramatically over the technology life cycle. These factors have implications for what forms of online crowds and communities are most likely to contribute technological advances. We provide a dynamic model of the expected "dominant communities" for technological advances at each phase of the life cycle, and we draw on examples from open-source software and consumer three-dimensional printing to illustrate the model. Our objectives are to determine how different forms of community-based innovation dominate at different times, to ground innovation models more firmly in material technological advances, and to provide focus for future research in this domain.